2015
DOI: 10.1002/jso.23963
|View full text |Cite
|
Sign up to set email alerts
|

Reversing the established order: Should adrenal venous sampling precede cross‐sectional imaging in the evaluation of primary aldosteronism?

Abstract: An AVS-first, imaging-second approach could have avoided CT/MRI in 43% of patients. At a high volume, experienced center, performing AVS first on patients with PA may reduce unnecessary cross-sectional imaging studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…As previously published, AVS was performed using a modified Mayo protocol . Selectivity index (SI) was calculated as adrenal/caval cortisol; AVS was considered technically successful with SI of ≥3.…”
Section: Methodsmentioning
confidence: 99%
“…As previously published, AVS was performed using a modified Mayo protocol . Selectivity index (SI) was calculated as adrenal/caval cortisol; AVS was considered technically successful with SI of ≥3.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies demonstrated that MRI has poorer resolution and slower acquisition than CT, with a risk of respiratory artefacts and that MRI is inferior to adrenal CT in PA subtype evaluation. [17][18][19][20] Contrast materials can improve the visibility of adrenal structures imaged by CT and MRI scans and might have a positive effect on diagnosis accuracy. 21 Thus, imaging methods and contrast materials were thought to be confounders for subgroup analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Its specificity is excellent, so much so that current guidelines recommend the use of cross-sectional imaging in conjunction with AVS [22]. However, to our knowledge the sensitivity of AVS has not been assessed as a function of left and right side cases, despite anatomical differences.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous publication, we reported on our experience in AVS and we insisted on those [6]. Preoperative AVS is mandatory for surgical decision making in the case of primary aldosteronism (PA) without any radiological target on abdominal CT scan, as it gives a definitive evaluation for the lateralization of PA [6, 22].…”
Section: Introductionmentioning
confidence: 99%